Perancangan Identitas Visual Annajah Vet Care, Pet & Poultry Shop Sebagai Upaya Meningkatkan Brand Awareness - Aldila Mahadevi Akhadiyatni; Aileena Solicitor Costa Rica El Chidtian; Widyasari Widyasari (Lembaga Pengembangan Kinerja Dosen, 2025)
Pets and livestock play an important role in everyday life, both economically and socially. However, both require optimal care and health to ensure their well-being and prevent potential health risks to humans. Annajah Vet Care, Pet & Poultry Shop comes as a veterinary clinic that provides comprehensive health services, such as vaccinations, hospitalization, grooming, and provision of feed for livestock and pets. Despite operating for two years, the clinic does not yet have a strong and consistent visual identity, as evidenced by the use of two similar logos that do not reflect the brand image. Promotion is also still limited to physical media and conventional methods such as word of mouth, with no utilization of social media. Surveys show that the majority of people recognize Annajah Vet Care as an animal health service provider, but brand awareness of its role as a pet shop is still low. To overcome this challenge, concept design was conducted as a strategic effort to strengthen brand identity through the application of a consistent and representative visual identity. In addition, the use of social media was optimized to reach a wider audience and support effective promotional efforts. Rebranding is expected to increase brand awareness, improve public perception of the services offered. With the right branding approach, Annajah Vet Care is expected to be able to compete in the market.